Assessing the seismic performance of rammed earth walls by using discrete elements. Issue 1 (31st December 2016) - Bui, Quoc-Bao; Bui, Tan-Trung; Limam, Ali
Abstract: Rammed earth (RE) is attracting renewed interest throughout the world because of its low embodied energy and its interesting hygric-thermal behavior. Several studies have recently been carried out to investigate this material. However, the seismic behavior of RE walls is still an important subject that needs to be more thoroughly investigated. The present study assesses the seismic performance of RE walls by using the discrete element modeling (DEM) and the nonlinear pushover method. Firstly, nonlinear "force–displacement" curves of the studied wall were obtained by DEM. Secondly, the standard "acceleration–displacement" curves were carried out following Eurocode 8. Thirdly, the above curves were superimposed to determine the intersection point (target point) which enabled to assess the seismic performance of the studied wall in the corresponding conditions (vertical load, seismic zone). The results show that the studied walls can have satisfactory resistance in seismicity zones ranging from "very low" to "moderate" (according to Eurocode 8). For "medium" seismicity zones, the studied structures should only be constructed on A-type soils (very good soil). For B-type soils, wall reinforcement techniques would be necessary. Without special reinforcements, studied RE structures seem unsuitable for "strong" seismicity zones, for all soil types.